Developing High-Quality Science and Technology Human Resources in Universities through Knowledge Transfer from International Science and Technology Projects: A Theoretical Approach - Thanh Tuan, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 40 No 4DO - 10.25073/2588-1116/vnupam.4533, 2024)
Universities are crucial in developing high-quality human resources for national development goals. In many countries, universities are regarded as the "cradle of talent," contributing to social progress and enhancing national competitiveness. Alongside their research function, universities serve as "incubators" for high-quality science and technology (S&T) human resources. In addition to training potential personnel such as students, graduate students, and doctoral candidates, universities are also hubs for knowledge transfer activities targeting high-quality S&T human resources. These efforts aim to cultivate a workforce capable of producing innovative and high-quality S&T products, thereby contributing significantly to national development. Accordingly, the implementation of international collaborative projects in the field of S&T has proven to be highly effective in facilitating multi-level knowledge transfer activities. Such initiatives enable universities to achieve streamlined and intelligent governance. Building upon theoretical frameworks and project management approaches, this paper will analyze the critical importance of promoting knowledge transfer activities for developing S&T human resources in universities. Furthermore, it proposes a specialized model for this knowledge transfer process through international S&T projects conducted within universities.